PENGARUH KEJELASAN SASARAN ANGGARAN, DESENTRALISASI DAN AKUNTABILITAS PUBLIK TERHADAP KINERJA MANAJERIAL SATUAN KERJA PERANGKAT DAERAH (Studi Empiris pada Satuan Kerja Perangkat Daerah Kabupaten Indragiri Hulu) - Vona Dwi Nugraha; Restu Agusti; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research examine the effect of Budget goal clarity, Decentralization and Public accountability on SKPD managerial performance. The population on this research were SKPD at Indragiri Hulu, and sample was determined based on judgement sampling method total 116 and use slovin formula, so that with 54 respondents. Collected with a direct survey using questionnaire that sent to Top and Middle manager at every selected SKPD in the region of Padang. Multiple regression analysis are used as analysis method with using Statistical Package For Social Science (SPSS) as the tools. This research proves that 1) Budget goal clarity significant positive impact on SKPD managerial performance (H1 accepted), 2) Decentralization significant negative impact on SKPD managerial performance (H2 rejected), 3) Public accountability significant negative impact on SKPD managerial performance (H3 rejected). From this research we can suggest that: 1) For all unit of government in Indragiri Hulu region to increase the implementation of budget goal clarity, decentralization and public accountability. It will give a good impact on managerial performances at the SKPD. 2) For future research, it is better to use a direct interview method to the respondent. So that the answer collected from the respondent are more clearly. 3) For future researcher, it is better to add the other related variable.Keywords: Budget goal clarity, Decentralization, Public accountability, Manajerial performance.